Please friends solve this.
Attachments:
![](https://hi-static.z-dn.net/files/d18/891153a1bc6d58447a2e2cb8ba05803e.jpg)
Answers
Answered by
1
1)
![p(x) = x {}^{3} + 2x {}^{2} + 3x + 2 p(x) = x {}^{3} + 2x {}^{2} + 3x + 2](https://tex.z-dn.net/?f=p%28x%29+%3D+x+%7B%7D%5E%7B3%7D++%2B+2x+%7B%7D%5E%7B2%7D++%2B+3x+%2B+2)
put -1 in eq.
![p( - 1) = ( - 1) {}^{3} + 2( - 1) {}^{2} + 3( - 1) + 2 p( - 1) = ( - 1) {}^{3} + 2( - 1) {}^{2} + 3( - 1) + 2](https://tex.z-dn.net/?f=p%28+-+1%29+%3D++%28+-+1%29+%7B%7D%5E%7B3%7D++%2B+2%28+-+1%29+%7B%7D%5E%7B2%7D++%2B+3%28+-+1%29+%2B+2)
![= - 1 + 2 - 3 + 2 = 0 = - 1 + 2 - 3 + 2 = 0](https://tex.z-dn.net/?f=+%3D++-+1+%2B+2+-+3+%2B+2+%3D+0)
Hence -1 satisfy thee equation so (x + 1) is a factor.
Now, f (x) ÷ g (x)
![(x {}^{3} + 2x {}^{2} + 3x + 2) \div (x + 1) (x {}^{3} + 2x {}^{2} + 3x + 2) \div (x + 1)](https://tex.z-dn.net/?f=%28x+%7B%7D%5E%7B3%7D++%2B+2x+%7B%7D%5E%7B2%7D++%2B+3x+%2B+2%29+%5Cdiv+%28x+%2B+1%29)
![(x {}^{2} + x + 2)(x + 1) (x {}^{2} + x + 2)(x + 1)](https://tex.z-dn.net/?f=%28x+%7B%7D%5E%7B2%7D++%2B+x+%2B+2%29%28x+%2B+1%29)
applying quadratic formula in
![x {}^{2} + x + 2 x {}^{2} + x + 2](https://tex.z-dn.net/?f=x+%7B%7D%5E%7B2%7D++%2B+x+%2B+2)
a =1 , b = 1 , c = 2
![x = (- b + - \sqrt{b {}^{2} - 4ac} ) \div 2a x = (- b + - \sqrt{b {}^{2} - 4ac} ) \div 2a](https://tex.z-dn.net/?f=x+%3D++%28-+b+%2B++-++%5Csqrt%7Bb+%7B%7D%5E%7B2%7D++-+4ac%7D+%29+%5Cdiv+2a)
![( - 1 + - \sqrt{(1) {}^{2} - 4(1)(2)} ) \div 2(1) ( - 1 + - \sqrt{(1) {}^{2} - 4(1)(2)} ) \div 2(1)](https://tex.z-dn.net/?f=%28+-+1+%2B++-++%5Csqrt%7B%281%29+%7B%7D%5E%7B2%7D++-+4%281%29%282%29%7D+%29+%5Cdiv+2%281%29)
![( - 1 + - \sqrt{ - 7} ) \div 2 ( - 1 + - \sqrt{ - 7} ) \div 2](https://tex.z-dn.net/?f=%28+-+1+%2B++-++%5Csqrt%7B+-+7%7D+%29+%5Cdiv+2)
So roots are
![(x + (1 + \sqrt{ - 7}) \div 2) (x + (1 + \sqrt{ - 7}) \div 2)](https://tex.z-dn.net/?f=%28x++%2B+%281+%2B++%5Csqrt%7B+-+7%7D%29++%5Cdiv+2%29)
![(x + (1 - \sqrt{ - 7} ) \div 2) (x + (1 - \sqrt{ - 7} ) \div 2)](https://tex.z-dn.net/?f=%28x+%2B+%281+-++%5Csqrt%7B+-+7%7D+%29+%5Cdiv+2%29)
![(x + 1) (x + 1)](https://tex.z-dn.net/?f=%28x+%2B+1%29)
2)
![p(x) = x {}^{3} - x{}^{2} - x + 1 p(x) = x {}^{3} - x{}^{2} - x + 1](https://tex.z-dn.net/?f=p%28x%29+%3D+x+%7B%7D%5E%7B3%7D++-++x%7B%7D%5E%7B2%7D++-+x+%2B+1)
put 1 in eq
![(1) {}^{3} - (1) {}^{2} - 1 + 1 (1) {}^{3} - (1) {}^{2} - 1 + 1](https://tex.z-dn.net/?f=%281%29+%7B%7D%5E%7B3%7D++-+%281%29+%7B%7D%5E%7B2%7D++-+1+%2B+1)
Hence 1 satisfied eq. so (x - 1) is a factor.
![(x {}^{3} - x {}^{2} - x + 1) \div (x - 1) (x {}^{3} - x {}^{2} - x + 1) \div (x - 1)](https://tex.z-dn.net/?f=%28x+%7B%7D%5E%7B3%7D++-+x+%7B%7D%5E%7B2%7D++-+x+%2B+1%29+%5Cdiv+%28x+-+1%29)
![(x {}^{2} - 1)(x - 1) (x {}^{2} - 1)(x - 1)](https://tex.z-dn.net/?f=%28x+%7B%7D%5E%7B2%7D++-+1%29%28x+-+1%29)
![(x - 1)(x + 1)(x - 1) (x - 1)(x + 1)(x - 1)](https://tex.z-dn.net/?f=%28x+-+1%29%28x+%2B+1%29%28x+-+1%29)
Thanks
put -1 in eq.
Hence -1 satisfy thee equation so (x + 1) is a factor.
Now, f (x) ÷ g (x)
applying quadratic formula in
a =1 , b = 1 , c = 2
So roots are
2)
put 1 in eq
Hence 1 satisfied eq. so (x - 1) is a factor.
Thanks
Similar questions